Anti-inflammatory Effect of Methanolic Extract of Mangifera Indica Leaves on Inflammed Rats in Comparison to Indomethacin - Nahar, Kamrun; Chowdhury, Iftekhar Hossain; Sultana, Sadia; Khan, Sharmin Jahan Khan; Fatema, Syeda Kaniz; Al Mamun, Md Abdullah (Mugda Medical College Journal, 2024)
In the context of inflammation and immunity, there are fragmented and observational studies relating the pharmacological effects of Mangifera indica leaves and its main active componentmangiferin. Hence, this study aims to evaluate the anti-inflammatory effects of this leaf extract (MIE) in comparison to Indomethacin on inflammed rats. The methanolic extract of Mangifera indica leaves in different doses, Indomethacin and normal saline were orally administrated in experimental and control groups of rats. Then acute inflammation was induced by administration of 0.1 ml of 1% Carrageenan in sterile saline solution into the sub-plantar surface of the right hind paw of each rat. Anteroposterior diameter of rat paw oedema was measured at 0 hour and at the end of 3 hours of Carrageenan injection. In the group treated with higher dose of methanolic extract of Mangifera indica leaves, acute inflammation in rats was improved significantly. But in the group treated with lower dose acute inflammation was not improved significantly in comparison to Indomethacin administered group. The methanolic extract of Mangifera indica (MEMI) leaves has potential health benefits as it showed dose dependent anti-inflammatory activity. The mangiferin in the MEMI leaves inhibits COX 2 enzyme and exerts the anti-inflammatory effects. Mugda Med Coll J. 2024; 7(1): 26-33